Pengaruh Profitabilitas, Likuiditas Dan Struktur Aset Terhadap Struktur Modal Dengan Ukuran Perusahaan Sebagai Variabel Moderating - Mukaromah, Dewi Uktani; Suwarti, Titiek (Universitas Pendidikan Ganesha, 2022)
This study aims to analyze and examine the effect of profitability, liquidity, and asset structure on capital structure with firm size as the moderating variable. The population used in this study is all property and real estate companies that have been listed on the Indonesia Stock Exchange (IDX) in the last three years, namely 2018-2020 as many as 182 companies. The sampling method used in this research is using purposive sampling technique which gets a sample of 172 companies and after being outliers to 141 companies. The data analysis method used in this research is Moderating Regression Analysis (MRA). The results of this study explain that liquidity has a negative effect on capital structure, liquidity has a negative effect on capital structure, while profitability has no effect on capital structure. Firm size moderates the effect of liquidity and asset structure on capital structure, but firm size does not moderate the effect of profitability on capital structure.Â Â Â